Variability for Seed Size, Oil Content, Seed Germination and Juvenile Traits in Germplasm Collections of SalvatlOl'a oleoit/es Decne from Arid Parts of Gujarat - Singh, S K; Singh, Manjit; Sivadasan, Rekha (Annals of Arid Zone, 2016)
Sa/vadora o/eoides Decne, a multipurpose tree. locally known as 'mitha jal', is found growing in dry and desert areas of Uttar Pradesh, Rajasthan, Haryana, Punjab, Gujarat and Madhya Pradesh. Its seeds are rich in non-edible oil. Fruits are eaten by local people, leaves are relished by animals; stem and branches are used for fuel. Arid parts of Gujarat and parts of Rajasthan adjoining Gujarat were explored in May 2003 for germplasm collection of S. o/eoides. Twenty-four accessions were collected from different sites and seed material deposited with National Bureau of Plant Genetic Resources, New Delhi. The seed oil content varied from 41.0% in Acc. No. SKJ 217 to 55.4% in Acc. No. SKJ 212 with a mean of 47.5%. Seeds of eight collections. out of 24, had more than 50% oil content.. Seed germination was 87.1 %. Three-month-old seedlings evaluated in nursery showed significant variation for plant height. nodes per plant, number of leaves per plant, leaf length and width. 100-seed weight and seed oil content were the only traits, which did not show any significant association with the seedling characters. Plant height had positive and significant association with number of nodes, number of leaves, leaf length and leaf width. Acc. No. SKJ 217 had best shape of tree, was free from witches broom, showed profuse and synchronous fruiting in situ, and had large, light red colored fruits with sweet taste and small seeds.